Metallized composite structure of photovoltaic solar cell and preparation method thereof

By printing a combined structure of the contact layer and the collection layer on the surface of the reflective layer of the photovoltaic solar cell, the problems of high cost and great environmental impact in the prior art are solved, and the effect of reducing the amount of silver used and maintaining high performance is achieved.

CN119653921APending Publication Date: 2025-03-18WUXI RUXING TECH DEV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411777119.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The metallization layer of existing photovoltaic solar cells mainly uses precious metal silver, which leads to high production costs and environmentally harmful, and the performance of traditional aluminum and copper in practical applications is insufficient.

Method used

By first printing the contact layer on the surface of the reflective layer, and then printing the collection layer, the combined structure of the contact layer and the collection layer is used to reduce the amount of silver paste, while forming a good contact for current transmission through high temperature sintering.

Benefits of technology

The silver cost of the metallized layer of photovoltaic cells is significantly reduced, while maintaining high performance, reducing production costs, reducing dependence on silver, reducing environmental impact, and improving the environmental sustainability of the photovoltaic industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119653921A_ABST
    Figure CN119653921A_ABST
Patent Text Reader

Abstract

The invention discloses a metalized composite structure of a photovoltaic solar cell and a preparation method of the metalized composite structure, and belongs to the technical field of photovoltaic solar cell manufacturing. The metallization composite structure comprises a substrate, a transmission layer, a reflection layer, a collection layer and a contact layer, the transmission layer is arranged on the surface of the substrate, the reflection layer is arranged above the transmission layer, the contact layer is arranged above the reflection layer, and the collection layer is printed on the surface of the contact layer. According to the invention, two kinds of mixed paste of the contact layer silver paste and the collection layer aluminum paste are used for replacing pure silver paste, so that the cell performance is met, the production cost price is reduced, the dependence on silver is reduced, the environmental influence caused by the acquisition of a silver raw material is reduced, and the environmental sustainability of the photovoltaic industry is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic solar cell manufacturing, and in particular to a photovoltaic solar cell metallization composite structure and a preparation method thereof. Background Art

[0002] Solar cells, especially crystalline silicon solar cells, are a core part of modern renewable energy technology. These cells achieve photoelectric conversion by forming a multilayer structure on a silicon substrate, in which the metallization layer plays a vital role. They are not only responsible for collecting and transmitting the current generated by the photogenerated charges, but also affect the efficiency and performance of the entire cell. Traditionally, these metallization layers are mainly made of silver (Ag) because of its excellent electrical conductivity and chemical stability. However, the price of silver is high, and its large-scale mining will have an impact on the environment. Therefore, seeking alternative materials with lower costs and less environmental impact is an urgent problem to be solved.

[0003] In the past few decades, the photovoltaic industry has undergone significant technological innovations, especially in metallization technology. Although aluminum (Al) and copper (Cu) have attracted research attention due to their lower cost and good electrical conductivity, their performance in practical applications still cannot fully match Ag. For example, Chang et al. (Chang YC, Zhang Y, Wang L, et al. Silver-lean metallization and hybrid contacts via plating on screen-printed metal for silicon solar cells manufacturing [J]. Progress in Photovoltaics: Research and Applications, 2024.) proposed a new screen-printed metallization hybrid electroplating method, which attempts to reduce the use of silver by plating copper on the silver grid line. However, if the copper layer is not properly treated, it is easy to form oxides in the environment, thereby reducing the efficiency and life of the battery. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a photovoltaic solar cell metallization composite structure and a preparation method thereof. The present invention provides a collection layer and a contact layer, and defines the contact layer and the collection layer slurry, so that the prepared metallization composite structure significantly reduces the production cost while maintaining high performance, providing a cost-effective solution for the photovoltaic cell industry.

[0005] The technical solution of the present invention is as follows:

[0006] A first aspect of the present invention provides a photovoltaic solar cell metallization composite structure, the metallization composite structure comprising a substrate 1, a transmission layer 2, a reflection layer 3, a collection layer 4, and a contact layer 5, the transmission layer 2 being arranged on the surface of the substrate 1, the reflection layer 3 being arranged above the transmission layer 2, the contact layer 5 being arranged above the reflection layer 3, and the collection layer 4 being printed on the surface of the contact layer 5.

[0007] Preferably, the transport layer 2 includes at least one of an electron transport layer and a hole transport layer; the reflective layer 3 includes at least one of a passivation reflective layer and an anti-reflective layer.

[0008] Preferably, the contact layer 5 has a thickness of 1-3 μm and a width of 5-10 μm; the collection layer 4 has a thickness of 3-20 μm and a width of 5-100 μm.

[0009] Preferably, the collection layer 4 is printed on the surface of the contact layer 5; the collection layer 4 has a thickness of 3-20 μm and a width of 12-100 μm.

[0010] Preferably, the content of silver powder in the slurry of the contact layer 5 is 80-90%.

[0011] Preferably, the silver powder in the slurry is at least one of spherical particles and flaky particles; and the particle size of the silver powder is 0.1-1.8 μm.

[0012] Preferably, the collection layer 4 includes at least one of an aluminum layer, a nickel-copper layer, a silver-nickel-copper layer, a copper-phosphorus layer, an Ag-Al layer, and a conductive organic coating.

[0013] Preferably, the slurry used for the aluminum layer comprises the following components by mass percentage: 70-80% aluminum powder, 15-28% organic binder, 1-3% inorganic binder, and 1-3% additives.

[0014] Preferably, the inorganic adhesive is inorganic glass powder; preferably, the softening point of the inorganic glass powder is 530-560°C; more preferably, the inorganic glass powder, by mass percentage, comprises the following raw materials: 15-30% SiO2, 6-12% B2O3, 12-15% ZnO, 25-40% Bi2O3, 5-10% Al2O3, 5-10% Li2O, 8-12% PbO.

[0015] The second aspect of the present invention provides a method for preparing the photovoltaic solar cell metallization composite structure according to the first aspect, comprising the following steps:

[0016] S1: depositing a transmission layer 2 on the surface of a substrate 1;

[0017] S2: Continue to deposit the reflective layer 3 on the surface of the transmission layer 2;

[0018] S3: preparing a slurry of the collecting layer 4 and a slurry of the contact layer 5;

[0019] S4: Printing the contact layer 5 on the surface of the reflective layer 3 and curing;

[0020] S5: Printing the collection layer 4 on the surface of the contact layer 5, curing and high-temperature sintering to obtain a photovoltaic solar cell metallization composite structure.

[0021] Preferably, in S1, the deposition includes at least one of diffusion deposition, chemical vapor deposition or physical deposition; in S2, the deposition includes at least one of atomic layer deposition and plasma enhanced chemical vapor deposition; in S4 and S5, the temperature of the drying and curing is 150-250°C; in S5, the temperature of the high temperature sintering is 600-850°C, and the time is 1-2min.

[0022] The beneficial technical effects of the present invention are:

[0023] The present invention prints a contact layer on the surface of the reflective layer first, and then prints a collection layer. The contact layer can achieve ohmic contact between the slurry and the substrate. The collection layer covers the surface of the contact layer, and forms a good contact for current transmission through high-temperature co-firing. The composite structure can reduce the amount of silver paste used, while meeting the cell photoelectric conversion efficiency. By using the composite structure to replace the silver paste-based grid line structure, the silver cost of the photovoltaic cell metallization layer can be significantly reduced (the amount of silver paste is reduced by more than 30%). The composite structure used reduces the production cost price while meeting the battery performance; at the same time, the introduction of non-silver raw materials in the composite structure reduces the amount of silver used, reduces the dependence on silver, and reduces the environmental impact caused by the acquisition of silver raw materials, which helps to improve the environmental sustainability of the photovoltaic industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic cross-sectional view of the photovoltaic solar cell metallization composite structure of the present invention.

[0025] In the figure: 1. Silicon substrate; 2. Transmission layer; 3. Reflection layer; 4. Collection layer; 5. Contact layer. DETAILED DESCRIPTION

[0026] The present invention is described in detail below.

[0027] Based on the current problems of photovoltaic solar cell metallization layer, the present invention provides a new photovoltaic solar cell metallization composite structure and its preparation method, aiming to solve the economic burden and performance limitations of using high-cost metals. By using lower-cost base metals or partially replacing silver paste, the production cost is significantly reduced without sacrificing battery performance, the market competitiveness of the product is improved, and new impetus is provided for the sustainable development of the photovoltaic industry.

[0028] A first aspect of the present invention provides a photovoltaic solar cell metallization composite structure, the metallization composite structure comprising a substrate 1, a transmission layer 2, a reflection layer 3, a collection layer 4, and a contact layer 5, the transmission layer 2 being arranged on the surface of the substrate 1, the reflection layer 3 being arranged above the transmission layer 2, the contact layer 5 being arranged above the reflection layer 3, and the collection layer 4 being printed on the surface of the contact layer 5.

[0029] The present invention prints a contact layer on the surface of the reflective layer first, and then prints a collection layer. The contact layer can achieve ohmic contact between the slurry and the substrate. The collection layer covers the contact layer, and a good contact is formed by high-temperature co-firing for current transmission. In some embodiments, the transmission layer 2 includes at least one of an electron transmission layer and a hole transmission layer; the reflective layer 3 includes at least one of a passivation reflective layer and an anti-reflection layer.

[0030] In some embodiments, the contact layer 5 has a thickness of 1-3 μm, including but not limited to 1 μm, 2 μm, and 3 μm, and a width of 5-10 μm, including but not limited to 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm; the collection layer 4 has a thickness of 3-20 μm, including but not limited to 3 μm, 5 μm, 7 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, and 20 μm, and a width of 5-100 μm, including but not limited to 5 μm, 7 μm, 9 μm, 10 μm, 12 μm, 15 μm, 20 μm, 25 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, and 100 μm.

[0031] In some embodiments, the collection layer 4 is coated and printed on the surface of the contact layer 5; the collection layer 4 has a thickness of 3-20 μm, including but not limited to 3 μm, 5 μm, 7 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, and 20 μm, and a width of 12-100 μm, including but not limited to 12 μm, 15 μm, 20 μm, 25 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, and 100 μm.

[0032] It can be understood that the collection layer 4 is printed directly on the contact layer 5 or the collection layer 4 is printed on the surface of the reflective layer 3 above the contact layer 5 and around the contact layer 5 (the cross-sectional schematic diagram is shown in FIG. Figure 1 As shown). The above-mentioned covering printing means that the collection layer 4 is printed on the surface of the reflection layer 3 above and around the contact layer 5. At this time, the width of the collection layer is larger than the contact layer, and the total thickness is 3-20 μm.

[0033] In some embodiments, the silver content in the paste of the contact layer 5 is 80-90%.

[0034] In some embodiments, other components of the slurry of the contact layer 5 are not limited, and any component and component combination that can achieve the effect of the present invention is within the protection scope of the present invention. Exemplarily, the slurry raw material of the contact layer 5 of the present invention includes the following components by mass percentage: 80-90% silver, 6-17% organic binder, and 2-3% inorganic glass powder.

[0035] In some embodiments, the silver powder in the slurry of the contact layer 5 is at least one of spherical particles and flaky particles; the particle size of the silver powder raw material is 0.1-1.8 μm and is normally distributed, and the particle size includes but is not limited to 0.1 μm, 0.5 μm, 1.0 μm, 1.5 μm, and 1.8 μm.

[0036] It is understood that the present invention does not limit the organic binder and inorganic glass used in the contact layer 5, and any organic binder and inorganic glass powder that can achieve the effect of the present invention are within the protection scope of the present invention. Exemplarily, the organic binder includes at least one of organic resin, sodium carboxymethyl cellulose, and hydroxypropyl methylcellulose. The inorganic glass powder is selected from at least one of phosphorus pentoxide-based glass powder and vanadium pentoxide-based glass powder.

[0037] It can be understood that the contact layer of the present invention can form a good ohmic contact with the substrate.

[0038] In some embodiments, the collection layer 4 includes at least one of an aluminum layer, a nickel-copper layer, a silver-nickel-copper layer, a copper-phosphorus layer, an Ag-Al layer, and a conductive organic coating, and may also be a copper hydride (CuH) layer.

[0039] It can be understood that in the present invention, the nickel-copper layer is a nickel-coated copper layer; the silver-nickel-copper layer is a copper layer coated with a mixture of silver powder and nickel powder; the copper-phosphorus layer is a copper-coated phosphorus layer; and the Ag-Al layer is a silver-coated aluminum layer.

[0040] It is understandable that the present invention does not limit the raw materials and preparation methods of the nickel-copper layer, silver-nickel-copper layer, copper-phosphorus layer, Ag-Al layer, and conductive organic coating, and any raw materials and preparation methods that can achieve the effects of the present invention are within the protection scope of the present invention. Exemplarily, the nickel-copper layer is prepared by mixing silver powder and nickel powder to prepare nickel-copper composite powder, adding additives, etc. to prepare slurry, and coating.

[0041] In some embodiments, the content of aluminum in the paste of the Ag—Al layer is greater than 70%.

[0042] In some embodiments, the conductive organic coating is a coating obtained by coating a slurry obtained by mixing a conductive material with an organic binder and an additive. The present invention does not limit its specific raw materials and preparation process, and any raw materials and preparation process that can achieve the effect of the present invention are within the protection scope of the present invention.

[0043] In some embodiments, the slurry used for the aluminum layer, namely aluminum paste, comprises the following components by mass percentage: 70-80% aluminum powder, 15-28% organic binder, 1-3% inorganic binder, and 1-3% additives.

[0044] In some embodiments, the slurry used for the aluminum layer includes the following components by mass percentage: 70-77% aluminum powder, 15-25% organic binder, 1-2% inorganic binder, and 1-3% additives.

[0045] It can be understood that the present invention uses aluminum paste as the collection layer and prints it on the contact layer silver paste, which reduces the amount of silver used, but there will be a large contact resistance between the silver paste and the aluminum paste, which affects the electrical performance. Therefore, by adjusting the inorganic adhesive in the aluminum paste, the contact resistance between the silver paste and the aluminum paste can be improved.

[0046] In some embodiments, the inorganic binder is inorganic glass powder.

[0047] In some embodiments, the softening point of the inorganic glass is 530-560°C, including but not limited to 530°C, 540°C, 550°C, and 560°C.

[0048] Preferably, the inorganic glass powder comprises the following raw materials by mass percentage: 15-30% SiO2, 6-12% B2O3, 12-15% ZnO, 25-40% Bi2O3, 5-10% Al2O3, 5-10% Li2O, and 8-12% PbO.

[0049] Combine 30% SiO2, 6% B2O3, 13% ZnO, 25% Bi2O3, 5% Al2O3, 9% Li2O, 12% PbO

[0050] In some embodiments, the inorganic glass powder includes the following raw materials by mass percentage: 21-30% SiO2, 9-12% B2O3, 12-14% ZnO, 25-32% Bi2O3, 5-8% Al2O3, 6-10% Li2O, and 8-10% PbO.

[0051] In some embodiments of the present invention, the inorganic adhesive is inorganic glass powder, and the preparation method is as follows: SiO2, B2O3, ZnO, Bi2O3, Al2O3, Li2O, and PbO are fully mixed in a mixer according to mass fraction, divided into porcelain crucibles, placed in an oven at 150°C, and baked for 2 hours; then placed in a high-temperature melting furnace at 1050°C for smelting, the smelting time is 1.5 hours, and after the smelting is completed, it is taken out and quenched in pure water. After the quenching is completed, the smelted solid is taken out and dried, and then crushed and ball-milled. After smelting and ball-milling, the median diameter of the inorganic adhesive particles is 3-5μm, and then water-solid separation is performed, and the separated solid-inorganic adhesive is dried in an oven at 150°C.

[0052] It is understandable that in the present invention, the aluminum paste is printed on the silver paste. During the high-temperature sintering process, the aluminum atoms will diffuse to the silver electrode layer, thereby promoting good contact between silver and aluminum. The inorganic glass powder plays a role of fluxing during the sintering process of the aluminum paste, but the glass powder will settle and gather at the silver-aluminum interface during the high-temperature melting process, which increases the silver-aluminum contact resistance and affects the electrical properties. Therefore, it is necessary to balance the high-temperature fluxing performance and fluidity of the glass powder. In the aluminum paste formula of the present invention, oxides with small molecular weight are used as the main glass material, thereby reducing the density of the glass, reducing the sedimentation and aggregation of the glass at the silver-aluminum contact surface during the melting process, and reducing the contact resistance; in addition, the high-viscosity inorganic glass powder prepared by the present invention can reduce the flow wettability of the glass in a high-temperature molten state.

[0053] In some embodiments, the organic binder includes 6-9% ethyl cellulose, 6-8% phenolic resin, 14-16% terpineol, 19-21% ethylene glycol dibutyl ether, 14-16% butyl carbitol, 24-26% diethylene glycol dibutyl ether, 4-6% lecithin, and 4-6% triethylene glycol monomethyl ether.

[0054] In some embodiments, the organic binder includes 8% ethyl cellulose, 7% phenolic resin, 15% terpineol, 20% ethylene glycol dibutyl ether, 15% butyl carbitol, 25% diethylene glycol dibutyl ether, 5% lecithin, and 5% triethylene glycol monomethyl ether.

[0055] In some embodiments, the organic binder is ethyl cellulose, phenolic resin, pinene alcohol, ethylene glycol dibutyl ether, butyl carbitol, diethylene glycol dibutyl ether, lecithin, triethylene glycol monomethyl ether, by mass fraction, put into a reactor, heat it with electric heating, stir at a speed of 60r / min, and keep the temperature at 120°C for 3 hours, wait for the resin and solvent in the reactor to be fully dissolved and mixed, cool it, and filter it with a 280-mesh screen.

[0056] The present invention significantly reduces the silver cost of the metallization layer of the photovoltaic cell by using two mixed slurries of contact layer silver slurry and collection layer aluminum slurry instead of pure silver slurry (the amount of silver slurry used is reduced by more than 30%). The mixed material used reduces the production cost price while meeting the battery performance; at the same time, the introduction of non-silver raw materials in the mixed material reduces the amount of silver used, reduces the dependence on silver, and alleviates the environmental impact caused by the acquisition of silver raw materials, which helps to improve the environmental sustainability of the photovoltaic industry.

[0057] The second aspect of the present invention provides a method for preparing the photovoltaic solar cell metallization composite structure according to the first aspect, comprising the following steps:

[0058] S1: depositing a transmission layer 2 on the surface of a substrate 1 .

[0059] S2: Continue to deposit the reflective layer 3 on the surface of the transmission layer 2.

[0060] S3: Prepare the slurry of the collection layer 4 and the slurry of the contact layer 5 .

[0061] S4: Printing the contact layer 5 on the surface of the reflective layer 3, and drying and curing.

[0062] S5: printing the collection layer 4 on the surface of the contact layer 5, drying and curing, and sintering at high temperature to obtain a photovoltaic solar cell metallization composite structure.

[0063] In some embodiments, in S1, the deposition includes at least one of diffusion deposition, chemical vapor deposition or physical deposition.

[0064] In some embodiments, in S1, the substrate includes a silicon substrate.

[0065] In some embodiments, in S2, the deposition includes at least one of atomic layer deposition and plasma enhanced chemical vapor deposition.

[0066] In S4 and S5, the curing temperature is 150-250°C, including but not limited to 150°C, 170°C, 190°C, 210°C, 230°C, and 250°C.

[0067] In S5, the high temperature sintering temperature is 600-850°C, including but not limited to 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, and the time is 1-2min, including but not limited to 1min, 1.5min, 2min.

[0068] It can be understood that in the present invention, the contact layer and the collection layer are processed by low-temperature drying and curing or laser technology or high-temperature sintering technology, which can ensure the excellent conductivity and mechanical stability of the battery structure.

[0069] In some embodiments, the contact resistance between the contact layer and the substrate of the present invention is less than 3mohm·cm 2 , line resistance is less than 1mohm / cm, and the contact resistance between the collection layer and the contact layer is less than 20mohm·cm 2 .

[0070] The metallized composite structure of the present invention significantly reduces production costs while maintaining high performance, providing a cost-effective solution for the photovoltaic cell industry. At the same time, the metallized composite structure design provided is highly adaptable and can use a variety of different materials and technology combinations to meet different production needs and performance standards. This design flexibility allows the present invention to be widely used in photovoltaic cell production of different types and scales.

[0071] The following are specific embodiments.

[0072] Example 1

[0073] A photovoltaic solar cell metallization composite structure, such as Figure 1 As shown, it includes a silicon substrate; an electron transport layer; a passivation reflective layer; a collection layer; and a contact layer.

[0074] The preparation method of the photovoltaic solar cell metallization structure is as follows:

[0075] (1) Cleaning the silicon substrate and forming an electron transport layer on the surface of the silicon substrate by chemical vapor deposition.

[0076] (2) A passivation reflective layer is formed on the surface of the electron transport layer by atomic layer deposition.

[0077] (3) Printing contact layer silver paste on the surface of the passivation reflective layer.

[0078] In this embodiment, the contact layer silver paste includes the following components by mass percentage: 85% silver, 13% organic binder, and 2% inorganic glass powder. The silver powder is spherical particles with an average particle size of 1.5 μm, the organic binder is an organic resin binder, and the inorganic glass powder is phosphorus pentoxide-based glass powder.

[0079] (4) curing the contact layer silver paste by chain drying at a temperature of 200°C;

[0080] (5) The collection layer slurry is continuously printed on the surface of the contact layer, and after curing at 200°C, it is sintered at a peak temperature of 740°C for 90 seconds to obtain a metallized composite structure. The thickness of the contact layer is 3 μm and the width is 10 μm, and the thickness of the collection layer is 15 μm and the width is 30 μm.

[0081] In this embodiment, the collection layer slurry includes 18.5% organic binder, 2% inorganic binder, 77% aluminum powder, and 2.5% additive.

[0082] Among them, the organic binder is 8% ethyl cellulose, 7% phenolic resin, 15% pineol, 20% ethylene glycol dibutyl ether, 15% butyl carbitol, 25% diethylene glycol dibutyl ether, 5% lecithin, and 5% triethylene glycol monomethyl ether, which are put into a reactor, heated by electric heating, stirred at a speed of 60r / min, and kept at a constant temperature of 120°C for 3 hours, until the resin and solvent in the reactor are fully dissolved and mixed, and then filtered with a 280-mesh screen after cooling.

[0083] The inorganic adhesive is inorganic glass powder, and the preparation method is as follows: 21% SiO2, 9% B2O3, 12% ZnO, 32% Bi2O3, 8% Al2O3, 10% Li2O, and 8% PbO are fully mixed in a mixer, divided into porcelain crucibles, placed in an oven at 150°C, and baked for 2 hours; then placed in a high-temperature smelting furnace at 1050°C for 1.5 hours, and after the smelting is completed, taken out and quenched in pure water. After the quenching is completed, the smelted solid is taken out and dried, and then crushed and ball-milled. After the smelting and ball-milling, the median diameter of the inorganic adhesive particles is 3-5μm, and then water-solid separation is performed, and the separated solid-inorganic adhesive is dried in an oven at 150°C.

[0084] The additives are a wetting and dispersing agent and a thixotropic agent in a mass ratio of 1:1.

[0085] Example 2

[0086] A photovoltaic solar cell metallization composite structure, whose structure is the same as that of embodiment 1.

[0087] The preparation method of the photovoltaic solar cell metallization composite structure is as follows:

[0088] (1) Cleaning the silicon substrate and forming an electron transport layer on the surface of the silicon substrate by chemical vapor deposition.

[0089] (2) A passivation reflective layer is formed on the surface of the electron transport layer by atomic layer deposition.

[0090] (3) Printing contact layer silver paste on the surface of the passivation reflective layer.

[0091] In this embodiment, the contact layer silver paste includes the following components by mass percentage: 85% silver, 13% organic binder, and 2% inorganic glass powder. The silver powder is spherical particles with an average particle size of 1.5 μm, the organic binder is an organic resin binder, and the inorganic glass powder is phosphorus pentoxide-based glass powder.

[0092] (4) curing the contact layer silver paste by chain drying at a temperature of 200°C;

[0093] (5) The collection layer slurry is continuously printed on the surface of the contact layer, and after curing at 200°C, it is sintered at a peak temperature of 740°C for 90 seconds to obtain a metallized composite structure. The thickness of the contact layer is 3 μm and the width is 10 μm, and the thickness of the collection layer is 15 μm and the width is 30 μm.

[0094] In this embodiment, the collection layer slurry includes 18.5% organic binder, 2% inorganic binder, 77% aluminum powder, and 2.5% additive.

[0095] Among them, the organic binder is 8% ethyl cellulose, 7% phenolic resin, 15% pineol, 20% ethylene glycol dibutyl ether, 15% butyl carbitol, 25% diethylene glycol dibutyl ether, 5% lecithin, and 5% triethylene glycol monomethyl ether, which are put into a reactor, heated by electric heating, stirred at a speed of 60r / min, and kept at a constant temperature of 120°C for 3 hours, until the resin and solvent in the reactor are fully dissolved and mixed, and then filtered with a 280-mesh screen after cooling.

[0096] The inorganic adhesive is inorganic glass powder, and the preparation method is as follows: 24% SiO2, 9% B2O3, 12% ZnO, 29% Bi2O3, 8% Al2O3, 10% Li2O, and 8% PbO are fully mixed in a mixer, divided into porcelain crucibles, placed in an oven at 150°C, and baked for 2 hours; then placed in a high-temperature smelting furnace at 1050°C for 1.5 hours, and after the smelting is completed, taken out and quenched in pure water. After the quenching is completed, the smelted solid is taken out and dried, and then crushed and ball-milled. After the smelting and ball-milling, the median diameter of the inorganic adhesive particles is 3-5μm, and then water-solid separation is performed, and the separated solid-inorganic adhesive is dried in an oven at 150°C.

[0097] The additives are a wetting and dispersing agent and a thixotropic agent in a mass ratio of 1:1.

[0098] Example 3

[0099] A photovoltaic solar cell metallization composite structure, whose structure is the same as that of embodiment 1.

[0100] The preparation method of the photovoltaic solar cell metallization composite structure is as follows:

[0101] (1) Cleaning the silicon substrate and forming an electron transport layer on the surface of the silicon substrate by chemical vapor deposition.

[0102] (2) A passivation layer is formed on the surface of the electron transport layer by atomic layer deposition.

[0103] (3) Printing contact layer silver paste on the surface of the passivation layer.

[0104] In this embodiment, the contact layer silver paste includes the following components by mass percentage: 85% silver, 13% organic binder, and 2% inorganic glass powder. The silver powder is spherical particles with an average particle size of 1.5 μm, the organic binder is an organic resin binder, and the inorganic glass powder is phosphorus pentoxide-based glass powder.

[0105] (4) curing the contact layer silver paste by chain drying at a temperature of 200°C;

[0106] (5) The collection layer slurry is continuously printed on the surface of the contact layer, and after curing at 200°C, it is sintered at a peak temperature of 740°C for 90 seconds to obtain a metallized composite structure. The thickness of the contact layer is 3 μm and the width is 10 μm, and the thickness of the collection layer is 15 μm and the width is 30 μm.

[0107] In this embodiment, the collection layer slurry includes 18.5% organic binder, 2% inorganic binder, 77% aluminum powder, and 2.5% additive.

[0108] Among them, the organic binder is 8% ethyl cellulose, 7% phenolic resin, 15% pineol, 20% ethylene glycol dibutyl ether, 15% butyl carbitol, 25% diethylene glycol dibutyl ether, 5% lecithin, and 5% triethylene glycol monomethyl ether, which are put into a reactor, heated by electric heating, stirred at a speed of 60r / min, and kept at a constant temperature of 120°C for 3 hours, until the resin and solvent in the reactor are fully dissolved and mixed, and then filtered with a 280-mesh screen after cooling.

[0109] The inorganic adhesive is inorganic glass powder, and the preparation method is as follows: 27% SiO2, 9% B2O3, 12% ZnO, 26% Bi2O3, 8% Al2O3, 10% Li2O, and 8% PbO are fully mixed in a mixer, divided into porcelain crucibles, placed in an oven at 150°C, and baked for 2 hours; then placed in a high-temperature smelting furnace at 1050°C for 1.5 hours, and after the smelting is completed, taken out and quenched in pure water. After the quenching is completed, the smelted solid is taken out and dried, and then crushed and ball-milled. After the smelting and ball-milling, the median diameter of the inorganic adhesive particles is 3-5μm, and then water-solid separation is performed, and the separated solid-inorganic adhesive is dried in an oven at 150°C.

[0110] The additives are a wetting and dispersing agent and a thixotropic agent in a mass ratio of 1:1.

[0111] Example 4

[0112] A photovoltaic solar cell metallization composite structure comprises a silicon substrate, an electron transport layer, a passivation reflection layer, a collection layer and a contact layer.

[0113] The preparation method of the photovoltaic solar cell metallization structure is as follows:

[0114] (1) Cleaning the silicon substrate and forming an electron transport layer on the surface of the silicon substrate by chemical vapor deposition.

[0115] (2) A passivation reflective layer is formed on the surface of the electron transport layer by atomic layer deposition.

[0116] (3) Printing contact layer silver paste on the surface of the passivation reflective layer.

[0117] In this embodiment, the contact layer silver paste includes the following components by mass percentage: 80% silver, 17% organic binder, and 3% inorganic glass powder. The silver powder is spherical particles with an average particle size of 0.5 μm, the organic binder is an organic resin binder, and the inorganic glass powder is phosphorus pentoxide-based glass powder.

[0118] (4) curing the contact layer silver paste by chain drying at a temperature of 150°C;

[0119] (5) The collection layer slurry is continuously printed on the surface of the contact layer, and after curing at 150°C, it is sintered at a peak temperature of 600°C for 120 seconds to obtain a metallized composite structure. The thickness of the contact layer is 3 μm and the width is 10 μm, and the thickness of the collection layer is 15 μm and the width is 30 μm.

[0120] In this embodiment, the collection layer slurry includes 28% organic binder, 1% inorganic binder, 70% aluminum powder, and 1% additive.

[0121] Among them, the organic binder is 9% ethyl cellulose, 8% phenolic resin, 16% pineol, 19% ethylene glycol dibutyl ether, 14% butyl carbitol, 25% diethylene glycol dibutyl ether, 5% lecithin, and 4% triethylene glycol monomethyl ether, which are put into a reactor, heated by electric heating, stirred at a speed of 60r / min, and kept at a constant temperature of 120°C for 3 hours, until the resin and solvent in the reactor are fully dissolved and mixed, and then filtered with a 280-mesh screen after cooling.

[0122] The inorganic adhesive is inorganic glass powder, and the preparation method is as follows: 30% SiO2, 6% B2O3, 13% ZnO, 25% Bi2O3, 5% Al2O3, 9% Li2O, and 12% PbO are fully mixed in a mixer, divided into porcelain crucibles, placed in an oven at 150°C, and baked for 2 hours; then placed in a high-temperature smelting furnace at 1050°C for 1.5 hours, and after the smelting is completed, taken out and quenched in pure water. After the quenching is completed, the smelted solid is taken out and dried, and then crushed and ball-milled. After the smelting and ball-milling, the median diameter of the inorganic adhesive particles is 3-5μm, and then water-solid separation is performed, and the separated solid-inorganic adhesive is dried in an oven at 150°C.

[0123] The additives are a wetting and dispersing agent and a thixotropic agent in a mass ratio of 1:1.

[0124] Example 5

[0125] A photovoltaic solar cell metallization composite structure, such as Figure 1 As shown, it includes a silicon substrate; an electron transport layer; a passivation reflective layer; a collection layer; and a contact layer.

[0126] The preparation method of the photovoltaic solar cell metallization structure is as follows:

[0127] (1) Cleaning the silicon substrate and forming an electron transport layer on the surface of the silicon substrate by chemical vapor deposition.

[0128] (2) A passivation reflective layer is formed on the surface of the electron transport layer by atomic layer deposition.

[0129] (3) Printing contact layer silver paste on the surface of the passivation reflective layer.

[0130] In this embodiment, the contact layer silver paste includes the following components by mass percentage: 90% silver, 7.5% organic binder, and 2.5% inorganic glass powder. The silver powder is spherical particles with an average particle size of 1.8 μm, the organic binder is an organic resin binder, and the inorganic glass powder is phosphorus pentoxide-based glass powder.

[0131] (4) curing the contact layer silver paste by chain drying at a temperature of 250°C;

[0132] (5) The collection layer slurry is continuously printed on the surface of the contact layer, and after curing at 250°C, it is sintered at a peak temperature of 850°C for 60 seconds to obtain a metallized composite structure. The thickness of the contact layer is 3 μm and the width is 10 μm, and the thickness of the collection layer is 15 μm and the width is 30 μm.

[0133] In this embodiment, the collection layer slurry includes 15% organic binder, 3% inorganic binder, 80% aluminum powder, and 2% additive.

[0134] Among them, the organic binder is 6% ethyl cellulose, 6% phenolic resin, 14% pineol, 21% ethylene glycol dibutyl ether, 16% butyl carbitol, 26% diethylene glycol dibutyl ether, 6% lecithin, and 5% triethylene glycol monomethyl ether, which are put into a reactor, heated by electric heating, stirred at a speed of 60r / min, and kept at a constant temperature of 120°C for 3 hours, until the resin and solvent in the reactor are fully dissolved and mixed, and then filtered with a 280-mesh screen after cooling.

[0135] The inorganic adhesive is inorganic glass powder, and the preparation method is as follows: 15% SiO2, 12% B2O3, 15% ZnO, 40% Bi2O3, 5% Al2O3, 5% Li2O, and 8% PbO are fully mixed in a mixer, divided into porcelain crucibles, placed in an oven at 150°C, and baked for 2 hours; then placed in a high-temperature smelting furnace at 1050°C for 1.5 hours, and after the smelting is completed, taken out and quenched in pure water. After the quenching is completed, the smelted solid is taken out and dried, and then crushed and ball-milled. After the smelting and ball-milling, the median diameter of the inorganic adhesive particles is 3-5μm, and then water-solid separation is performed, and the separated solid-inorganic adhesive is dried in an oven at 150°C.

[0136] The additives are a wetting and dispersing agent and a thixotropic agent in a mass ratio of 1:1.

[0137] Comparative Example 1

[0138] A photovoltaic solar cell metallization composite structure, whose structure is the same as that of embodiment 1.

[0139] The preparation method of the photovoltaic solar cell metallization composite structure is basically the same as that of Example 1, except that the collection layer slurry used is a commercially available double-sided PERC aluminum slurry, including 18.5% organic binder, 2% inorganic binder, 77% aluminum powder, and 2.5% additive. The inorganic binder includes 15% SiO2, 6% B2O3, 15% ZnO, 40% Bi2O3, 6% Al2O3, 6% Li2O, and 12% PbO.

[0140] Test example:

[0141] The solar cells containing the metallized composite structure prepared in the examples and comparative examples were subjected to photoelectric conversion efficiency tests and contact resistance tests, and the performance of the photovoltaic solar cells prepared in the examples 1-3 and comparative examples was measured. The results are shown in the following table.

[0142] Table 1 Photoelectric conversion efficiency test of the embodiments and comparative examples

[0143] Slurry Voc Isc FF Eta Rs Comparative Example 1 0.7144 14.7517 79.863 23.309 0.00196 Example 1 0.7183 14.8084 79.854 23.523 0.00182 Example 2 0.7165 14.8014 80.276 23.577 0.00176 Example 3 0.7189 14.7995 80.199 23.63 0.00177

[0144] It can be seen from Table 1 that the photoelectric conversion efficiency of the solar cell prepared in the embodiment is better.

[0145] Table 2 Contact resistance of embodiments and comparative examples

[0146]

[0147] It can be seen from Table 2 that the silver-aluminum contact resistance of the solar cell prepared in the example is significantly lower than that in the comparative example, and the contact resistance of Example 3 is the smallest.

[0148] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.

Claims

1. A photovoltaic solar cell metallization composite structure, characterized in that: The metallized composite structure comprises a substrate (1), a transmission layer (2), a reflection layer (3), a collection layer (4), and a contact layer (5); the transmission layer (2) is arranged on the surface of the substrate (1); the reflection layer (3) is arranged above the transmission layer (2); the contact layer (5) is arranged above the reflection layer (3); and the collection layer (4) is printed on the surface of the contact layer (5).

2. The metallized composite structure according to claim 1, characterized in that: The transport layer (2) includes at least one of an electron transport layer and a hole transport layer; The reflective layer (3) comprises at least one of a passivation reflective layer and an anti-reflective layer.

3. The metallized composite structure according to claim 1, characterized in that: The contact layer (5) has a thickness of 1-3 μm and a width of 5-10 μm; the collection layer (4) has a thickness of 3-20 μm and a width of 5-100 μm.

4. The metallized composite structure according to claim 1, characterized in that: The collection layer (4) is printed on the surface of the contact layer (5); the collection layer (4) has a thickness of 3-20 μm and a width of 12-100 μm.

5. The metallized composite structure according to claim 1, characterized in that: The content of silver powder in the slurry of the contact layer (5) is 80-90%; Preferably, the silver powder is at least one of spherical particles and flaky particles; and the particle size of the silver powder is 0.1-1.8 μm.

6. The metallized composite structure according to claim 1, characterized in that: The collection layer (4) comprises at least one of an aluminum layer, a nickel-copper layer, a silver-nickel-copper layer, a copper-phosphorus layer, an Ag-Al layer, and a conductive organic coating.

7. The metallized composite structure according to claim 6, characterized in that: The slurry used for the aluminum layer includes the following components by mass percentage: 70-80% aluminum powder, 15-28% organic binder, 1-3% inorganic binder, and 1-3% additive.

8. The metallized composite structure according to claim 7, characterized in that: The inorganic binder is inorganic glass powder; Preferably, the softening point of the inorganic glass powder is 530-560°C; More preferably, the inorganic glass powder comprises the following raw materials by mass percentage: 15-30% SiO2, 6-12% B2O3, 12-15% ZnO, 25-40% Bi2O3, 5-10% Al2O3, 5-10% Li2O, and 8-12% PbO.

9. A method for preparing the photovoltaic solar cell metallization composite structure according to any one of claims 1 to 8, characterized in that: The steps include: S1: depositing a transmission layer (2) on the surface of a substrate (1); S2: Continue to deposit a reflective layer (3) on the surface of the transmission layer (2); S3: preparing a slurry for the collection layer (4) and a slurry for the contact layer (5); S4: printing a contact layer (5) on the surface of the reflective layer (3), and drying and curing the layer; S5: Printing the collection layer (4) on the surface of the contact layer (5), drying and curing, and sintering at high temperature to obtain a photovoltaic solar cell metallization composite structure.

10. The preparation method according to claim 9, characterized in that: In S1, the deposition includes at least one of diffusion deposition, chemical vapor deposition, and physical deposition; In S2, the deposition includes at least one of atomic layer deposition and plasma enhanced chemical vapor deposition; In S4 and S5, the drying and curing temperature is 150-250°C; In S5, the high temperature sintering is performed at a temperature of 600-850° C. and a time of 1-2 minutes.